Business Process Improvement on Capital Projects Evaluation System at PT. Freeport Indonesia - Zefrinardi, Rendy; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2012)
Underground area, in particular is focusing on sub-area Underground and sub-area Long- Term Development, have business development projects with high-intensive capitals and as a consequence also have extraordinary business risks. This areas would be revenue sources for PTFI for the next ten years of operations, 2011-2021.This final project aims to initiate an optimization of business process in capital project evaluation system with emphasis to underground area, with objectives to increase PTFI resources capability to conduct capital project forecast, projects evaluation and projects approvals and authorization according to company policy.Approach taken by conducted root-cause-analysis to find source of issue by referencing three-year capital projects performance for mentioned sub-areas, and field survey to active project users to identify and analyze source of issues that leads to steps for improvement. Process tools utilized are Issue Tree, Severity Matrix dan FCX PMO (Project Management Office) Methodology.Source of issues found in sub-areas of Underground is that total actual cost in comparison to projected forecast project cost, in cumulative for the past three years.  There are arising business requirements to optimize capital projects evaluation system to specifically address project cost forecast in Underground and Long-Term Development sub-areas.   Other than that an end-to-end interconnection is necessary starts from a request for project budget submitted, project evaluation process, to decision making process where it ties approvals for budget authorization up to company’s director level into a single system.Recommended solution to be applied is to optimize process in project evaluation system to get and prepare more accurate projects cost estimate, accountable and consider business risks to support capital management on capex projects in PTFI. Key words:  business process improvement, project evaluation system, authorization for expenditure, capex, finance process improvement.